2016
DOI: 10.1111/cch.12368
|View full text |Cite
|
Sign up to set email alerts
|

Parenting children with intellectual disabilities in Malawi: the impact that reaches beyond coping?

Abstract: Apart from suicide and filicide, the findings of this study are similar to those performed in other countries. It is recommended that parents' psychological issues be managed concurrently when providing services for their children. There is also a need to develop psychosocial training interventions to address the needs of the parents of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 34 publications
7
64
1
1
Order By: Relevance
“…The low mood and sense of helplessness expressed by the caregivers was associated with a lack of support, both within the family and externally in the community as reported previously [5,6,10,17,24). Indeed, the common experience was one of psychological stress and daily challenges, which concurs with the work of Masulani-Mwale [26]. The burden of caregiving appeared to be related to a lack of agency or control over the events that challenged on a daily basis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The low mood and sense of helplessness expressed by the caregivers was associated with a lack of support, both within the family and externally in the community as reported previously [5,6,10,17,24). Indeed, the common experience was one of psychological stress and daily challenges, which concurs with the work of Masulani-Mwale [26]. The burden of caregiving appeared to be related to a lack of agency or control over the events that challenged on a daily basis.…”
Section: Discussionsupporting
confidence: 63%
“…Zimmerman and colleagues [31][32][33][34]58] might explain this as the antithesis of empowerment. Having a child with a disability was considered generally incongruent with acceptability in the prevailing culture, and indeed triggered negative responses from others in the family and in the community as reported previously [4,5,[17][18][19][21][22][23][24][25][26]. Thus both caregiver and child were effectively marginalised in their own community, with a lack of knowledge, limited support and no opportunity for joining their efforts with others-critical components of the empowerment construct described by Perkins & Zimmerman [58].…”
Section: Discussionmentioning
confidence: 95%
“…We assume that if there are communication difficulties, understanding becomes complicated. Based on the literature, we believe attitudes towards disability would improve with interaction and information [ 48 ]. Further studies would be recommended to clarify this possible relation.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers have addressed that mothers can burnout, become depressed, and experience suicidal ideation when caring for children with physical disabilities, which may lead to neglect or abuse of the child. (14,41,42) One Malawian study reported marriage breakdowns as a consequence of a child's CM. (7) In response, caregivers have described the need for peer support groups, and healthcare workers have suggested group counselling for caregivers of children with neurodisabilities.…”
Section: Resultsmentioning
confidence: 99%